hERG K+ Channels Promote Survival of Irradiated Leukemia Cells - Palme, Daniela; Misovic, Milan; Ganser, Katrin; Klumpp, Lukas; Salih, Helmut R.; Zips, Daniel; Huber, Stephan M. (Frontiers in Pharmacology, 2020)
Many tumor cells express highly elevated activities of voltage-gated K+ channels in the plasma membrane which are indispensable for tumor growth. To test for K+ channel function during DNA damage response, we subjected human chronic myeloid (CML) leukemia cells to sub-lethal doses of ionizing radiation (0, 1 or 5 Gy, 6 MV photons) and determined K+ channel mRNA and protein abundance, K+ channel activity, K+-channel dependent Ca2+ signaling, cell cycle progression, and clonogenic survival by RT-PCR, Western Blotting, whole-cell patch clamp recording, fura-2 Ca2+ imaging, flow cytometry, and pre-plating colony formation assay, respectively. As a result, the human erythroid CML cell line K562 and primary human CML cells expressed isoforms of hERG1. Irradiation stimulated in both cell types an increase in the activity of hERG1 K+ channels which became apparent 1-2 h post-irradiation. This increase in K+ channel activity was paralleled by an increase in Ca2+ entry and followed by accelerated G1/S cell cycle transition and subsequent S and G2/M cell cycle arrest as analyzed between 8 and 72 h post-irradiation. Attenuating the K+ channel function by applying the hERG1 channel inhibitor E4031 markedly increased radiation-induced Ca2+ entry, impaired inhibition of the mitosis promoting subunit cdc2, overrode cell cycle arrest and decreased clonogenic survival of the irradiated cells suggesting a critical role of the hERG1 K+ channels for the Ca2+ signaling and the cell cycle control during DNA damage response.